Effects of cyclooxygenase inhibition on insulin release and pancreatic islet blood flow in rats - Sandberg, Monica (Ups J Med Sci, 2014)
OBJECTIVES: To examine the effects of inhibition of cyclooxygenase (COX) on islet hormone secretion in vitro and on pancreatic islet blood flow in vivo. METHODS: Insulin release was measured in a static incubation system of islets isolated from Wistar-F rats after inhibition of COX-1 and COX-2 with SC 560 (COX-1), FR 122047 (COX-1), rofecoxib (COX-2), or indomethacin (both COX-1 and COX-2). In other rats organ blood flow values were measured with a microsphere technique during both normo- and hyperglycemia after administration of these enzyme inhibitors. RESULTS: Serum insulin values were lower after pretreatment with a COX-1 inhibitor or a non-selective COX inhibitor in both control and glucose-injected rats in vivo, whereas COX-2 inhibition had no such effects. However, inhibition of COX had only minor effects on insulin release in vitro. Inhibition of COX affected neither total pancreatic nor islet blood flow in normoglycemic rats. Hyperglycemia caused an increase in both these flow values and in the duodenum. The increase in total pancreatic and duodenal blood flow was prevented by inhibition of COX-2 or non-selective COX inhibition. However, no effects on islet blood flow were seen after COX inhibition. CONCLUSION: Inhibition of COX affects insulin release and blood glucose concentrations in vivo. However, COX inhibition has only minor effects on pancreatic islet blood flow, but prevents the glucose-induced increase in total pancreatic blood flow.